Suburban air quality: Human health hazard assessment of potentially toxic elements in PM10. (June 2017) - Megido, Laura; Suárez-Peña, Beatriz; Negral, Luis; Castrillón, Leonor; Fernández-Nava, Yolanda
Abstract: PM10 samples were collected at two suburban locations in northern Spain, a traffic-industrial suburban (TIS) station located in the coastal city of Gijón and an industrial suburban (IS) station in Langreo, about 25 km inland. The aerosol samples were chemically analysed to determine ambient air concentrations of As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Se, V and Zn. The results showed that the mean levels of As, Co, Cu, Fe, Mn, Ni, Pb and Se recorded at the IS location were higher than those at the TIS station. Mean levels of Fe and Zn in PM10 were higher than all other species at both the TIS and IS sampling sites (467 and 353 ng Fe/m 3 and 46 and 282 ng Zn/m 3, respectively). Human exposure to these twelve potentially toxic elements through PM10 was assessed for both children and adults using the U.S.EPA method, considering three pathways: ingestion, dermal contact and inhalation. In general, the IS location presented higher non-cancer risks than the TIS site. However, at both suburban locations, cancer and non-cancer risk values were in the acceptable range for adults, some exceptions being found. Greater health risk was estimated in the case of children. For this sector of the population, ingestion, dermal contact and/or inhalation of As, Pb and Zn in PM10 may pose a health hazard owing to possible carcinogenic/non-carcinogenic effects. Highlights: Health risk due to PM10 was assessed for children and adults at two suburban sites. Health risk was higher for residents at the industrial site than at the traffic site. Cancer and non-cancer risks were below the safe limit for adults. As, Pb and Zn in PM10 posed higher potential health risk for children than adults.